Bayesian uncertainty quantification to identify population level vaccine hesitancy behaviours - David J. Warne; Abhishek Varghese; Aidan Brewster; Alexander P. Browning; Mario M. Krell; Christopher Drovandi; Wenbiao Hu; Antonietta Mira; Kerrie Mengersen; Adrianne L. Jenner (PLoS ONE, 2026)
When effective vaccines are available, vaccination programs are typically one of the best defences against the spread of an infectious disease. Such vaccination programs become particularly important during severe epidemics or pandemics to ensure sufficient vaccination coverage is achieved to increase protection or reduce transmission to a level that enables relaxation of non-pharmaceutical interventions, such as lockdowns, travel restrictions, or social distancing. Unfortunately, vaccination uptake in the community may be slow if there are substantial levels of vaccine hesitancy in the population. As a result, it is important to identify when these hesitancy behaviours are present in the community. Furthermore, understanding the main drivers of such behaviour can inform adjustments to public health strategies to improve community uptake. In this study, we consider the problem of identifying vaccination hesitancy behaviour during a vaccination roll-out that occurs in response to a severe epidemic. Specifically, our aim is to explore the extent to which mathematical modelling of reported case, death, and vaccination counts can be used to detect vaccine hesitancy and possible drivers. To do this, we develop a novel susceptible-exposed-infectious-recovered (SEIR) epidemiological model of disease transmission that incorporates changes in population behaviour relating to non-pharmaceutical interventions and vaccine uptake that are influenced by information reported through media or data dashboards about cases, deaths, and vaccination rates. We then use a Bayesian approach to analyse simulated data representing various hesitancy scenarios. Through this simulation study, our key findings are that individual parameters values related to drivers of vaccine hesitancy often cannot be identified. However, posterior correlation structures between these parameters enable the presence of vaccine hesitancy in the community to be detected and provide some insight into the relative influence of key factors, such as vaccine safety concerns or complacency. While our simulation study is inspired by the public health response to the COVID-19 pandemic, our tools and techniques are general and could enable vaccination programs of various infectious diseases to be adapted rapidly in response to community behaviours in the future.